RANCANG BANGUN DIGITAL SIGNAGE BERBASIS MIROKOMPUTER RASPBERRY PI 3B - Syukri Gazali Suatkab; Thenny Daus Salamoni; Laura Stefanny Nunumette; Melda Dahoklory, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Information is very important and valuable. With the right information, decisions can be made. The government of Tawiri conveys information using information media such as bulletin boards or banners to the people of the country and visitors. Unfortunately, information through these media is not easy to manage because it takes time to design information, deliver designs, print, or install it. Updates that may only be minor still require these processes to be carried out. For this reason, research was conducted on the implementation of digital signage using raspberry microcomputers. The research method used was research and development to design and build a system consisting of hardware (display monitor, Raspberry Pi) and software (system and application software). The system was built using the Raspberry Pi 3 Model B microcomputer. Although not the best version of raspberry, Raspberry Pi 3 has proven to be usable as a digital signage content player. The test results collected related to the Raspberry Pi 3 response time to several scenarios were identified as the impact of the playlist